Capital formation and regional disparities in Canada since the 1960s. - Bougrine, Hassan. (University of Ottawa (Canada), 1992)
Regional disparities are a fact of Canadian life. Large income disparities among regions have persisted for a long time. Disparities in employment opportunities are also substantial. The location of key economic sectors is highly concentrated and this has resulted in a highly regionalized industrial structure. The existence of such disparities has preoccupied both academics and politicians, but few of their efforts aimed at reducing these disparities have been successful. A review of previous research shows that although traditional economic theory has long considered capital accumulation at the heart of the growth process, regional analysis in Canada has largely ignored the importance of capital formation in determining relative economic fates of the various regions of the country. The central issue of this study has been to examine the role which capital accumulation has played in regional disparities in Canada since the 1960s. Two main questions were addressed. The first question considers the extent to which the regional distribution of capital stocks has affected growth in regional output, productivity, and employment. The thesis has established some strong correlations between patterns of growth of capital stocks on the one hand, and regional economic disparities in output, productivity, and employment on the other hand. A detailed examination of the regional dynamics of capital accumulation in Canada shows that regional investment is strongly influenced by the relative growth rate of a region, the relative size of its capital stock, local labour costs adjusted for productivity, and the level of past profits. The thesis found that one of the impediments to rapid growth of capital accumulation in the poorer regions is the limited availability of finance. Access to capital has an important influence on capital accumulation and, therefore, on regional growth. The effect of capital accumulation on productivity growth is estimated from a productivity function which relates growth in productivity to growth in output, growth in capital-labour ratio, and technical progress. It is found that regional differences in the intensity of capital have played an important role in labour productivity differences. The second question looks at the type of policy to be implemented in order to reduce regional disparities by altering the present pattern of capital accumulation. The thesis proposed a model of optimal allocation of investment funds that takes into account both objectives of national growth and regional equity. The model is based on optimal control theory and considers both the maximization of national income and minimization of regional inequalities in one objective function. It is shown that in such a case the optimal policy is not to concentrate investment in the more prosperous regions, but to increase capital where it is scarce. This will stimulate growth in the poor regions and provide opportunity to reduce disparities in employment and income.
Keywords: Economics, General.